A STUDY OF SIRIP DESA AT CITERAS, LEBAK, BANTEN AN ARCHIEVAL INFORMATION SYSTEM - Ria Astriratma; Helena Nurramdhani Irmanda (Kresnamedia Publisher, 2021)
This study aims to create an archiving information system that can be used to store data held by government officials in Citeras Village as needed. The research stage was preceded by collecting data archives / files contained in the Citeras Village Village. Then the data is processed to be processed in the system. The data obtained is modeled according to system requirements. Then implemented into a web-based system. The output of this research is the availability of an archiving information system as a data storage tool in accordance with the needs of the web-based Citeras Village government device using the SDLC (System Development Life Cycle) Waterfall method. Database design using MySQL and the programming language used is PHP. The result of this research is the availability of a web-based archiving information system for population data in Citeras Village which can then be used by Citeras Village officials, Rangkasbitung District, Lebak Regency, Banten.